Pemodelan Sistem Peramalan Kebutuhan Spare Part Menggunakan Unified Modeling Language - Finna Suroso; Gita Mustika Rahmah; Denny Riandhita AP (Fakultas Ilmu Komputer dan Desain - Unsurya, 2023)
In the business world, technology can be used as a tool for all activities carried out in business including monitoring the needs of a spare part. This is done in an effort to help the progress of a business. Most workshops have anticipated the need for spare parts in transactions, but the unavailability of spare parts when there is demand and overstock spare parts, still occurs, causing losses in the workshop. It is very important for the forecasting system, especially regarding the need for the availability of spare parts in the workshop. In design, the information system forecasting the needs of spare parts uses Unified Modeling language (UML) modeling to analyze what is needed and what will be built. UML is a tool to help systems and methodologies that can be used for the development of an object-oriented system. We can more easily create a system with UML modeling, because in UML there are already all the things that will be designed. In addition, if we make UML first, the implementation of a system will be an accurate system. Modeling the Forecasting System for Spare Part Needs using UML is expected to be a tool that can help business actors to be able to advance their business and get optimal profits.